3-5x=-1-6x

Simple and best practice solution for 3-5x=-1-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-5x=-1-6x equation:



3-5x=-1-6x
We move all terms to the left:
3-5x-(-1-6x)=0
We add all the numbers together, and all the variables
-5x-(-6x-1)+3=0
We get rid of parentheses
-5x+6x+1+3=0
We add all the numbers together, and all the variables
x+4=0
We move all terms containing x to the left, all other terms to the right
x=-4

See similar equations:

| 22=4+6w | | 0.2(x+500)=3,750 | | 3x2=2x4 | | 4x+35x-15=8x-1 | | -2x^2+5x-10=0 | | 2/3x-15=-5 | | 8x^2-8=-27 | | x/3x+10=22 | | 3x+19+5x+12=180 | | 4z-6+2z=3z+9 | | 2(b+24)=138-7b | | x+(3x-7)=77 | | 6x-4=-13 | | 3/4(8x+12)=3(2x+3) | | 6(x-2)+x=5x-1 | | 3c4= | | 3x+2+5x+12=180 | | K=2m=5 | | 3(-4)=-1/2(24-6x) | | 32=-8+8b | | 82+31+x=180 | | -7=x(-3) | | 29x+8=205 | | n/6=8/3 | | -161=7(5-4n) | | 3^2w^2-8^2=0 | | 4(×-2)=2(x-4)+2× | | 6k=19.8 | | 10x-4-2x=x+10 | | 7y-2y=24 | | 12=z/6-30 | | 40(4y-9)=5y |

Equations solver categories